2011
DOI: 10.1126/science.1206027
|View full text |Cite
|
Sign up to set email alerts
|

The Persistently Variable “Background” Stratospheric Aerosol Layer and Global Climate Change

Abstract: Recent measurements demonstrate that the "background" stratospheric aerosol layer is persistently variable rather than constant, even in the absence of major volcanic eruptions. Several independent data sets show that stratospheric aerosols have increased in abundance since 2000. Near-global satellite aerosol data imply a negative radiative forcing due to stratospheric aerosol changes over this period of about -0.1 watt per square meter, reducing the recent global warming that would otherwise have occurred. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
565
1
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 548 publications
(593 citation statements)
references
References 26 publications
19
565
1
8
Order By: Relevance
“…Their effect is visible in the increase of the stratospheric aerosol layer that has occurred since 2002 after a period with little volcanic influence. This increase in the stratospheric aerosol load has also been observed in other data sets, however, anthropogenic influence cannot be ruled out (Hofmann et al, 2009;Solomon et al, 2011).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Their effect is visible in the increase of the stratospheric aerosol layer that has occurred since 2002 after a period with little volcanic influence. This increase in the stratospheric aerosol load has also been observed in other data sets, however, anthropogenic influence cannot be ruled out (Hofmann et al, 2009;Solomon et al, 2011).…”
mentioning
confidence: 51%
“…However studies indicate that OCS is not enough to explain the observed aerosol load (Chin and Davis, 1995), and direct transport of SO 2 or sulphate aerosol have been suggested as important contributions to stratospheric aerosol (Pitari et al, 2002;Myhre et al, 2004). Volcanic injections however makes it difficult to determine the background state of the stratospheric aerosol layer (Solomon et al, 2011), and thereby the importance of different sources for its production. A carbonaceous component of the UT/LMS aerosol was identified by Murphy et al (1998), which was subsequently found to be a large fraction of the aerosol (Nguyen et al, 2008;Murphy et al, 2007).…”
mentioning
confidence: 99%
“…Occasionally chemical elements connected with crustal matter and fires are observed (Papaspiropoulos et al, 2002), which on rare occasions can have a strong influence on aerosol particle concentration (Eguchi et al, 2009;Dirksen et al, 2009;Fromm et al, 2010). Particles from explosive volcanism have strong effects on the studied region at times, affecting the climate (Ammann et al, 2003;Solomon et al, 2011), stratospheric ozone (McCormick et al, 1995) and aviation (Gislason et al, 2011). The aerosol particles in volcanic clouds contain besides the ash component (Schumann et al, 2011;Andersson et al, 2013) large sulphurous and carbonaceous components (Martinsson et al, 2009;Schmale et al, 2010;Carn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1). Two schools of idea exist regarding what causes this hiatus of global warming: one suggests a slowdown in radiative forcing due to the stratospheric water vapour 3 , the rapid increase of stratospheric and tropospheric aerosols 4,5 , and the solar minimum around 2009 (ref. anomalies in the equatorial eastern Pacific (8.2% of the Earth surface) follow the observed evolution (see Methods).…”
mentioning
confidence: 99%